1990
DOI: 10.1177/109019819001700208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Understanding of Popular Press Reports of Health Research

Abstract: This research assessed the ability of a sample of persons on a college campus to understand media reports of health research. Three or four articles on each of five contemporary health topics (dietary cholesterol and heart disease, treatment for breast cancer, starch blockers, drug treatment for heart disease, test tube skin) were selected from widely circulated newspapers (e.g., New York Times) and magazines (e.g., Newsweek). A sample of 144 college students responded to content-based and application-based qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…Two-thirds of America's cancer deaths can be linked to behavioral factors such as tobacco, diet, obesity, and a lack of physical activity [52]. As cancer diagnoses escalate, the media and the public are turning more attention to health [4,53]. If the cancer epidemic is to be abated, the news media and the sources they turn to for cancer information can likely have a considerable effect on the public's health.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Two-thirds of America's cancer deaths can be linked to behavioral factors such as tobacco, diet, obesity, and a lack of physical activity [52]. As cancer diagnoses escalate, the media and the public are turning more attention to health [4,53]. If the cancer epidemic is to be abated, the news media and the sources they turn to for cancer information can likely have a considerable effect on the public's health.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The news media are a primary source of new health information for physicians and the lay public alike (e.g., Niederdeppe et al, 2007;Phillips, Kanter, Bednarczyk, & Tastad, 1991;Yeaton, Smith, & Rogers, 1990). While widespread critiques of the quality of cancer news coverage abound (e.g., Freimuth, Greenberg, DeWitt, & Romano, 1984), factual disagreements between published scientific results and news reporting of them are rare (Bubela & Caulfield, 2004;Condit, 2004;Moyer, Greener, Beauvais, & Salovey, 1994).…”
Section: News Coverage About Cancermentioning
confidence: 99%
“…News media reports are one of the primary ways the public learns about new findings and changes in medical science (Johnson, 1997;Yeaton et al, 1990), but news reports often distill study findings into simple messages, obscuring complexities (e.g., Stryker, 2002). Our results have dual implications in this context.…”
Section: Study Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only half the students demonstrated knowledge of the elements of scientific argument. Furthermore, Yeaton et al (1990) found that university students can also be overly accepting of generalizations of health-related research extracted from newspapers and magazines. Thus, our future adult citizens are graduating from the school system without the skills necessary to accurately interpret scientific information.…”
Section: Early Science Literacy: What Do Trade Books Contribute?mentioning
confidence: 97%